Role of Modified Biophysical Profile in Prediction of Fetal Asphyxia - Nadia Sadiq, Nargis Shabana, Aqsa Ikram Ul Haq, Shama Bashir, Nabeela Waheed, Jaweria Faisal (Journal of Rawalpindi Medical College, 2021)
Objective To determine the diagnostic accuracy of Modified Biophysical Profile (MBPP) in determining fetal asphyxia in high risk pregnancies keeping actual birth asphyxia on Apgar Score as gold standard. Patients and Methods After written informed consent from patients, 235 patients with high risk pregnancies admitted to obstetric ward unit 2 Holy Family Hospital were enrolled in study. BPP was done by modified method in high risk patient at > 36 week gestation. Amniotic fluid index was calculated by measuring 4 quadrant vertical pockets and if sum of 4 pockets was< 5 it was considered as abnormal. Total score in MBPP is 4.Out of which 2 score for CTG and 2 score of AFI. These patients were followed till delivery and newborn will be assessed at the time of delivery for fetal asphyxia. Fetal asphyxia was assessed on the basis of Apgar score at 5 min after birth. All patients delivering beyond 7 days of MBPP was excluded from the study. Results Mean age (years) in our study was 27.11+1.47 whereas mean parity was 2+1.06 with ranges from nulliparous to para four. The sensitivity, specificity, positive predicative value and negative predicative value of Modified Biophysical Profile (MBPP) in determining fetal asphyxia in high risk pregnancies keeping actual birth asphyxia on Apgar score as gold standard was 95.02%, 71.43%, 98.13% and 47.62% respectively. Conclusion MBPP was found to have high sensitivity and positive predictive value in predicting fetal asphyxia as assessed by Apgar score at birth. Key words: Modified Biophysical profile, Perinatal outcome, High risk pregnancies, Non stress test